Experimental and numerical approach to titanium-aluminum explosive welding. (2nd September 2021) - Wu, Xiaoming; Shi, Changgen; Feng, Ke; Gao, Li; Li, Wenxuan; Qian, Kun
Abstract: The welding parameters of TA2/1060/5083 were calculated accurately through a combination of explosive welding weldability window and numerical simulation, based on which explosion welding experiments were conducted using these parameters obtained. Then, a test was carried out on the mechanical properties of the composite plates obtained from the experiments and microstructure characterization was performed. As suggested by the results, TA2/1060 was a excellent straight bond, and the interface of 1060/5083 was a sine-wave featuring both vortex structure and splashing molten block structure, with an average wavelength of 700 μ m and a wave height of 100 μ m. The tensile strength and shear strength of the composite materials reached 354 MPa and 110 MPa, respectively, while the material showed the signs of ductile fracture. Moreover, work hardening and fine grain strengthening occurred at the interface, as did the element diffusion of Ti-Al, with a maximum diffusion depth of 32 μ m.